Celecoxib prevents malignant progression of smoking-induced lung tumors via suppression of the COX-2/PGE2 signaling pathway in mice - Sakurai, Kaori; Chubachi, Shotaro; Miyata, Jun; Hamamoto, Junko; Naganuma, Tatsuro; Shimada, Takashi; Otake, Shiro; Nakayama, Shingo; Irie, Hidehiro; Tsutsumi, Akihiro; Kameyama, Naofumi; Hegab, Ahmed E.; et al. (Frontiers in Immunology, 2025)
IntroductionLung cancer is characterized by a poor prognosis and is a significant comorbidity of chronic obstructive pulmonary disease (COPD). Therefore, effective chemopreventive agents are warranted. We evaluated the effects of the cyclooxygenase-2 (COX-2) inhibitor celecoxib on the prevention of lung-carcinoma development using an intermittent smoking-induced lung-carcinoma mouse model. Additionally, we explored COX-2’s role in lipid metabolism.MethodsMale A/J mice were exposed to sham air or mainstream cigarette smoke for 20 weeks. Vehicle or celecoxib was administered via intragastric feeding once daily. Lung tissues were analyzed for tumor nodules and emphysema; the bronchoalveolar lavage fluid was collected for cell counting. COX-2 expression was measured using real-time polymerase chain reaction and western blotting; lipidomic analysis was conducted using liquid chromatography-tandem mass spectrometry. Cell proliferation and colony-forming assays were performed on LA-4 cells to assess the effects of prostaglandins and COX-2 inhibitors.ResultsIntermittent smoking exposure increased lung adenomas, adenocarcinomas, and COX-2 expression. Lung adenomas were characterized by abundant COX-2-positive cells. Celecoxib reduced intermittent smoking-induced inflammation, emphysema, and cell counts in the bronchoalveolar lavage fluid and decreased the incidence of lung adenocarcinomas, whereas the total number of observed lung tumors was unchanged. Celecoxib markedly suppressed single-smoke-induced prostaglandin E2 (PGE2) production in the airway. PGE2 increased LA-4 cell viability via the EP4 receptor and promoted colony formation.DiscussionCelecoxib effectively inhibited lung-carcinoma development, inflammation, and emphysema, demonstrating the potential for chemoprevention in smokers and patients with COPD. Further studies on EP4 inhibitors for the prevention of emphysema and lung cancer are warranted.